Novedades y notas taxonómicas en especies de Senecio de la Patagonia, Argentina - Tortosa, Roberto Daniel (2014)
Fil: Tortosa, Roberto Daniel. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.